ON THE POETICAL PROPERTIES OF SYMBOLIC IMAGES IN 20TH CENTURY LITERATURE (Scientific journal of the Fergana State University, 2025)
Article considers the issue of using symbols in world and uzbekliterature and their meaning and interpretation by readers in works of authors such as M. Bulgakov “Master and Margaret”, Ernest Hemingway “The snow of Kilimanjaro” and “Cat in the rain”, A. Camus “Le Peste”, Omon Muhtar “Plato”, N. Eshonqul “Coffin”, HurshidDustmuhammad “Jajman” and “Ibn Muganniy”.